2013
DOI: 10.1007/s00109-013-1058-5
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of gap junctions in melanoma and their impact on Melan-A/MART-1-specific CD8+ T lymphocyte emergence

Abstract: GJ formation occurs in vivo between T lymphocytes and tumor cells Cx43 localized at the immunological synapse between T and autologous melanoma cells Inhibition of GJs resulted in a decrease in Ag-specific CD8(+) T lymphocyte induction A role for GJs in the regulation of antigen CD8(+)-naïve T lymphocyte activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…It has been reported in vitro as well as in situ that human naïve CD8 + T cells establish GJCs with melanoma target cells, contributing to their activation, but not to their lytic function [240]. Conversely, human NK cells establish GJCs with DCs and tumor cells in a Cx43-dependent process that contributes to NK cell-mediated lysis and further antitumoral immunity (Figure 7) [107].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported in vitro as well as in situ that human naïve CD8 + T cells establish GJCs with melanoma target cells, contributing to their activation, but not to their lytic function [240]. Conversely, human NK cells establish GJCs with DCs and tumor cells in a Cx43-dependent process that contributes to NK cell-mediated lysis and further antitumoral immunity (Figure 7) [107].…”
Section: Discussionmentioning
confidence: 99%
“…NK92 and MCF7 cells were obtained from the ATCC. Cells were maintained in culture as described previously (7). NK cells were maintained in RPMI medium supplemented with 300 units/ml recombinant human IL-2.…”
Section: Methodsmentioning
confidence: 99%
“…Because Cxs have short half-lives, their turnover regulation and trafficking critically impact the control of GJmediated intercellular communication (5). Connexin 43 (Cx43), the main GJ protein found in immune cells (6), has been shown recently to accumulate at the immunological synapse and allows GJ-mediated intercellular communication between effector immune and tumor target cells (7)(8)(9)(10). These observations suggest that loss of Cx43 expression during tumor progression may represent a mechanism by which cancer cells evade immune control by the local microenvironment (11).…”
mentioning
confidence: 99%
“…In human melanoma biopsies, it has been demonstrated that Cx43 is expressed between tumor and endothelial cells and between T-cells and cancer cells, indicative of GJ formation [54]. This study proposed that GJs between these cells regulate the formation of an immunological synapse among T lymphocytes and autologous melanoma cells [106]. In this model, the opening of Cx43 HCs has been associated with cytokine release by T-cells and regulation of Ca 2+ oscillations among T cells.…”
Section: Expression Of Connexins and Pannexins In Immune Cellsmentioning
confidence: 99%